Meningkatkan Aktivitas Dan Prestasi Belajar Siswa MTs At-Tahzib Kekait Melalui Model Pembelajaran Conceptual Understanding Prosedures (CUPs) Tahun Pelajaran 2016/2017 - Hidayati, Wahida; Sukarma, I Ketut; pujilestari, pujilestari (Universitas Pendidikan Mandalika (UNDIKMA), 2017)
The background of this study is the low activity and student achievement in learning mathematics is still one of the causes of low quality education, especially in math. One effort to further streamline the learning of mathematics is to apply the learning model Conceptual Understanding Prosedures (CUPS). The purpose of this research is to improve the activity and student achievement MTs At-Tahzib Kekait VIII class A through learning model Conceptual Understanding Prosedures (CUPS). This research was conducted in MTs At-Tahzib Kekait in class VIII A. The method used was classroom action research. The instrument used in this study is the observation sheet student activities, teacher activity observation sheet, and test evaluation. By applying the learning model Conceptual Understanding Prosedures (CUPS) in mathematics. Activities and student achievement during the learning process is increasing. This fact is shown by the acquisition of an average score of student activity in cycle I and II respectively of 2.55 and 3.16. In addition didikung by an increase in student achievement is increasing. This is evidenced by the average value of the test results of the evaluation cycle I and II is 68.59 with classical completeness of 58.33% and 78.87 with classical completeness of 87.5% in the second cycle. Based on the analysis of data that the application of learning models Conceptual Understanding Prosedures (CUPS) by increasing the activity and student achievement MTs At-Tahzib Kekait VIII grade A academic year 2016/2017.Â